Suillusgrevillei and Suillus luteus promote lead tolerance of Pinus tabulaeformis and biomineralize lead to pyromorphite - Cheng, Kang; Liu, Yaqin; Tang, Ming; Zhang, Haoqiang (Frontiers in Microbiology, 2024)
Lead (Pb) is a hazardous heavy metal that accumulates in many environments. Phytoremediation of Pb polluted soil is an environmentally friendly method, and a better understanding of mycorrhizal symbiosis under Pb stress can promote its efficiency and application. This study aims to evaluate the impact of two ectomycorrhizal fungi (Suillus grevillei and Suillus luteus) on the performance of Pinus tabulaeformis under Pb stress, and the biomineralization of metallic Pb in vitro. A pot experiment using substrate with 0 and 1,000 mg/kg Pb2+ was conducted to evaluate the growth, photosynthetic pigments, oxidative damage, and Pb accumulation of P. tabulaeformis with or without ectomycorrhizal fungi. In vitro co-cultivation of ectomycorrhizal fungi and Pb shots was used to evaluate Pb biomineralization. The results showed that colonization by the two ectomycorrhizal fungi promoted plant growth, increased the content of photosynthetic pigments, reduced oxidative damage, and caused massive accumulation of Pb in plant roots. The structural characteristics of the Pb secondary minerals formed in the presence of fungi demonstrated significant differences from the minerals formed in the control plates and these minerals were identified as pyromorphite (Pb5(PO4)3Cl). Ectomycorrhizal fungi promoted the performance of P. tabulaeformis under Pb stress and suggested a potential role of mycorrhizal symbiosis in Pb phytoremediation. This observation also represents the first discovery of such Pb biomineralization induced by ectomycorrhizal fungi. Ectomycorrhizal fungi induced Pb biomineralization is also relevant to the phytostabilization and new approaches in the bioremediation of polluted environments.